ANALISIS DEBIT AIR DENGAN VARIASI BENTUK OPEN CHANNEL DENGAN PENAMPANG SEGITIGA, PERSEGI, DAN TRAPESIUM PADA SUATU ALIRAN - Kun Suharno; Catur Pramono; Sigit Mujiarto; Kurniawan Setyo Anggoro (Journal of Mechanical Engineering, 2019)
An open channel is a channel where water flows with free water. In open channels, such as rivers (natural channels), channel parameters are very irregular. Damming the channel is a transition that serves to determine the height of the water surface along the channel, on this issue the author examines how water flows when through open channel with v-notch, rectangular and trapezoidal shapes in a stream. Based on the test results on 35° valve angle variations, the increase debit from the v-notch debit leads to a rectangular-notch debit of 23.63% and the largest decrease in debit from the rectangular notch to trapezodial-notch is 48.38%. In the valve angle variation 40°, the largest increase in debit between the v-notch discharge towards a rectangular-notch discharge of 18.64% and the decrease in the largest debit from  rectangular-notch to trapezodial-notch at 45.31%. In the valve angle variation 45° the largest increase debit between the v-notch debit towards a rectangular-notch debit is 18.64% and the largest decrease debit from the rectangular notch to trapezodial-notch debit is 46.15%.